Growth Performance, Carcass Yield and Organosomatic Indices of Clariasgariepinus Fed Propolis and Ag-zyme as Dietary Additives - Muniru , Adewole, Adeyemo; Oluwaseyi , Awosusi, Ayokunle (African Journal of Education,Science and Technology (AJEST), 2015)
In order to achieve self-sufficiency in fish production and supply in the subsequent years, cultured fish must be adequately fed diet to promote growth using additives.This study evaluated the effects of aqueous propolis extract and Ag-Zyme on growth performance, carcass yield and organosomatic indices of Clariasgariepinus. Eight isonitrogenous diets containing 40% Crude Protein: Control (0%), AGZ1 (0.35%), AGZ2 (0.7%), AGZ3 (1.4%), PRP1 (0.5%), PRP2 (1%), PRP3 (2%) and PRP4 (4%) were formulated. 15 fingerlings were stocked per treatments in triplicates and fed 5% body weight for 84days.Mean Weight Gain (MWG), Specific Growth Rate (SGR), Relative Growth Rate (RGR), Feed Conversion Ratio (FCR), carcass yield, percentage dress out, body weight yield and organosomatic indices were measured using standard methods. Data were 0.05).The result revealed that the MWG,SGR,RGR ranged from 37.21g to 70.00g; 0.57g to 0.83g;621.23g to 1250.00g respectively. The highest MWG was from fish fed PRP2 diet, closely followed by AGZ3 diet and the least from the control diet. The highest FCR (3.4) was from the control diet and the least from the fish fed PRP2 diet (2.52).Percentage (%) dress out and carcass yield showed no significant (p>0.05) difference across the treatments. Highest body weight yield was from PRP4 (101.43±3.89), closely followed by PRP2 diet (99.31±0.33) and the least was from AGZ3diet (74.22±8.01). Head yield showed significant (p<0.05) difference across the treatments. Hepatosomatic (HIS), Renosomatic(RSI), Visceralsomatic (VSI), Gillsomatic (GSI) and Fat deposit indices (FDI) showed significant (p<0.05) difference, while Cerebrosomatic (CBI) and Cardiosomatic(CSI) indices did not vary significantly among the diets. Propolis (PRP2) gave the best growth and could be recommended in practices, as dietary additive for optimal growth of Clariasgariepinus without necessarily compromising the health integrity of the fish. Alternatively, Agzyme (AGZ3) can also be used as alternative to propolis.